Pelatihan Pembuatan Vermikompos di Desa Lokasi Baru Kecamatan Air Periukan Kabupaten Seluma - Agung Trisusilo; Indra Cahyadinata (UNIB Press, 2021)
This activity aims to increase the awareness of the people of Lokasi Baru Village to make animal manure into compost using the vermicomposting method. The method used in this activity is a combination of counseling and structured training. The result of this activity is that participants are able to see the potential resources they have in the form of animal manure and process it into vermicompost fertilizer which is more useful and has economic value. In practice, participants experienced problems at the stage of preparation of developmental media, hatching of worm eggs, and the composting process. Although in the implementation process the participants faced several obstacles, with assistance from the service team they were able to resolve these obstacles independently. After participating in this series of activities, the participants learned that the livestock waste they produce has economic value if managed properly. Therefore, at this time they have been practicing the knowledge gained independently. Keywords: shit livestock; Lumbricus sp.; vermicompost